The Phoenix lights [videorecording (DVD)] : beyond top secret - Kitei, Lynne D., 1948- (Vanguard, 2010)
Review for yourself one doctor's firsthand experiences, months of documentation, and startling photographs of a V-shaped formation of lights that mysteriously flew over a town in Arizona, catching the attention of major national media publications.